Pengaruh Digital marketing dan Keragaman Produk terhadap Proses Keputusan Pembelianpada Marketplace Shopee (Study kasus pada Mahasiswa Institut STIAMI Kampus Perluasan Bekasi B) - Liza Umami; Anita Maulina (JAMBIS : Jurnal Administrasi Bisnis, 2022)
This study aims to explain: The Effect of Digital (X1) Marketing and Product Diversity (X2) on the Purchase Decision Process (Y) at the Shopee Marketplace at the STIAMI Institute Campus, Bekasi Expansion B. The research population refers to Shopee users on the Institute Campus in this study. STIAMI expansion Bekasi B. The sample in this study used a purposive sampling method with a total of 125 respondents, and the data collection method used a questionnaire. Based on the study results, the following regression equation was obtained: Y= 11.012+0.183X1+0.310X2. Based on statistical data analysis, the indicators in this study are valid and the variables are reliable. The equation shows that Digital marketing and Product Diversity influence the Purchasing Decision Process. The conclusions drawn are: 1) Digital marketing has a positive effect on the Purchase Decision Process This is based on regression analysis (t test) it is known that tcount>ttablenamely 7,713 > 1,979 and a significance value of 0.000 < 0.05 with a partial determination coefficient of 21.6%. 2) Product diversity has a positive effect on the Purchasing Decision Process. It is based on regression analysis (t test). It is known that tcount>ttable namely 6.386 > 1.979 and a significance value of 0.000 < 0.05 with a partial determination coefficient of 24.9%. 3) Digital marketing and Product Diversity on the Purchasing Decision Process This is based on regression analysis (t test). It is known that fcount>ftable, namely 34.572 > 3.07 and a significance value of 0.000 < 0.05. 4) the coefficient of determination (R2) simultaneously that Digital marketing on Product Diversity through the Purchase Decision Process has an effect of 36.2% and other variables influence the rest.